Frequency of Hydrocephalus in Patients with Spontaneous Intracerebral Hemorrhage (ICH) at Chandka Medical College Hospital Larkana - Sana Ghous Shaikh, Abu Bakar Shaikh, Nagina Shaikh, Alam Ibrahim Siddiqui, Aijaz Ali, Mohsin Irshad (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The small rupture of vessels damaged due to HTN (Hypertension) or amyloid angiopathy is the causative agent of ICH (Intracerebral Hemorrhage). There is strong association of Spontaneous ICH with high rate of morbidity as well as in hospital mortality. Other important factors include altered conscious level, hematoma volume, midline shift, intraventricular extension, high blood pressure and renal dysfunction. Objective: The rationale of this research study was to find out the rate of occurrence of hydrocephalus among patients who suffered from spontaneous ICH and to observe the in-hospital outcome for these patients having hydrocephalus. Methodology: The design of this study was descriptive, cross-sectional study. Patients of spontaneous ICH admitted to the Neurology Department CMC Hospital, Larkana were the samples of this study and the duration of this study was from June 2021 to November 2021. Total 87 patients were the participants of this research study. Hypertension was confirmed through clinical record or two readings ten minutes apart. Diabetes was diagnosed through clinical record or through HbA1C. CT scan brain was done. The diagnosis of spontaneous ICH was carried out on the basis of the clinical and radiological criteria and admitted for further diagnosis of hydrocephalus and in-hospital outcome. We calculate the descriptive statistics. We performed the stratification with the utilization of Chi square test considering the P-value of ≤ 0.050 as much significant. Results: Total 59.80% male and 40.20% female patients were the subjects of this research work. Mean age and BMI was 35.63±10.13 years and 26.69±7.92 kg/m2 respectively. The frequency of hydrocephalus with spontaneous intra-cerebral hemorrhage (ICH) was found in 58.60% patients and their in-hospital mortality was recorded in 49.40% cases. Conclusion: A significant number (58.60%) of patients of ICH were having hydrocephalus and it has a strong association with the high rate of mortality 49.40%.